2005
DOI: 10.1159/000085773
|View full text |Cite
|
Sign up to set email alerts
|

Can Teachers’ Behavior Ratings Be Used to Screen Early Adolescent Boys for Psychiatric Diagnoses?

Abstract: The present study examined if a short, 22-item teacher rating questionnaire could be used to screen young adolescent boys for psychiatric diagnoses. Subjects were 239 12-year-old boys from a community sample of low socioeconomic status families. Child and parent versions of the Diagnostic Interview Schedule for Children were used to provide DSM-III-R diagnoses. Results show a low to moderate screening value for the Short Social Behavior Questionnaire (S-SBQ) scales, with best results for externalizing disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…The first gate of the screening process involved teacher ratings of students’ aggressive behaviors. Although teacher ratings of children’s conduct problem behaviors in general (e.g., Hill et al, 2004; Kassing et al, 2019), and aggressive behavior in particular (Carbonneau et al, 2005; Hodgins et al, 2013; Verhulst et al, 1994; Whipp et al, 2019) have been found to have validity in predicting students’ long-term outcomes, and do so better than parent ratings, the potential for teacher bias in behavior ratings also exists. Teacher race has been found to affect their ratings of children’s behavior from the preschool years (Wymer et al, 2022; Yoder & Williford, 2019) through the later school years (Redding, 2019), with Black children found to have lower ratings of externalizing behavior problems when rated by Black teachers.…”
Section: Methodsmentioning
confidence: 99%
“…The first gate of the screening process involved teacher ratings of students’ aggressive behaviors. Although teacher ratings of children’s conduct problem behaviors in general (e.g., Hill et al, 2004; Kassing et al, 2019), and aggressive behavior in particular (Carbonneau et al, 2005; Hodgins et al, 2013; Verhulst et al, 1994; Whipp et al, 2019) have been found to have validity in predicting students’ long-term outcomes, and do so better than parent ratings, the potential for teacher bias in behavior ratings also exists. Teacher race has been found to affect their ratings of children’s behavior from the preschool years (Wymer et al, 2022; Yoder & Williford, 2019) through the later school years (Redding, 2019), with Black children found to have lower ratings of externalizing behavior problems when rated by Black teachers.…”
Section: Methodsmentioning
confidence: 99%
“…Elementary school teachers spend most of every school day with their pupils and are able to rate each child, as compared with many other children of the same sex and age. Teacher ratings of externalizing problems are reliable, 15 concurrently associated with externalizing disorders, 16 and predictive of future externalizing behaviour. 17 However, knowledge of the validity of teacher ratings for predicting criminal offending through adolescence and early adulthood is limited.…”
Section: Limitationsmentioning
confidence: 96%
“…Teacher-rated measures of behavioral problems have also shown high reliability [13][14][15]. Furthermore, studies have shown that teacher ratings of problem behaviors have often been more useful than parent ratings in diagnostic and predictive outcomes, including psychiatric disorders and criminality [7,10,16,17]. Teachers' ability to observe children in a structured setting and among peers of similar ages and abilities provides them with a valuable comparison-base, making their insight important.…”
Section: Introductionmentioning
confidence: 99%